The Name Is the Game: Nicknames as Predictors of Personality and Mating Strategy in Online Dating - Lange, Benjamin P.; von Andrian-Werburg, Maximilian T. P.; Adler, Dorothea C.; Zaretsky, Eugen (Frontiers in Communication, 2019)
Objective: We investigated the communicative function of online dating user names. Our aim was to assess if it is possible to correctly guess personality traits of a user simply by reading his/her nickname. Method: We had 69 nickname users (average age: 33.59 years, 36 female) complete questionnaires assessing their personality (Big 5 + narcissism) and mating strategy (short- vs. long-term). We then checked (using a total of 638 participants, average age: 26.83 years, 355 female), whether personality and mating strategy of the nickname users could be assessed correctly based only on the nickname. We also captured the motivation to contact the user behind a nickname and looked at linguistic features of the nicknames. Results: We found that personality and mating strategy could be inferred from a nickname. Furthermore, going by trends, women were better at intersexual personality judgments, whereas men were better in intrasexual judgements. We also found several correlates of the motivation to con-tact the person behind the nickname. Among other factors, long nicknames seemed to deter people from contacting the nickname user. Conclusions: Findings display that humans are capable of making accurate personality judgements in computer-mediated communication by means of even small cues like nicknames.